2019
DOI: 10.1021/acs.jcim.8b00958
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density in Enzyme Active Site as a Descriptor of Electrostatic Preorganization

Abstract: Large protein macromolecules in enzymatic catalysis have been shown to exert a specific electric field that reduces the reorganization energy upon barrier crossing and thus reduces the reaction free energy barrier. In this work we suggest that the charge density in the active site of an enzyme investigated using formalisms embodied by the quantum theory of atoms in molecules (QTAIM) provides a sensitive and quantum field-reactant state charge density-reaction barrier correlation. Hence, QTAIM can be used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 52 publications
6
90
0
Order By: Relevance
“… 13 Recent independent analysis using quantum theory of atoms in molecules (QTAIM) reported a significant correlation between charge density, external electric field, and activation energy changes in KSI. 29 These results obtained by entirely different methodologies are complementary with ours reinforcing conclusions in both studies. This is in line with the well-known proton-coupled electron-transfer effects.…”
Section: Resultssupporting
confidence: 85%
“… 13 Recent independent analysis using quantum theory of atoms in molecules (QTAIM) reported a significant correlation between charge density, external electric field, and activation energy changes in KSI. 29 These results obtained by entirely different methodologies are complementary with ours reinforcing conclusions in both studies. This is in line with the well-known proton-coupled electron-transfer effects.…”
Section: Resultssupporting
confidence: 85%
“…There are also reports about the effects of electric fields (both in the inorganic and biological milieu) on chemical reactions, as the field can significantly alter the potential energy curves near the transition state region governing chemical reactions [8] and consequently influence course and rate constants of the reactions [9][10][11][12]. Most effects can be comprehended as the field-induced stabilization of ionic structures [16].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] One of the most studied enzymes in the context of understanding electrostatic preorganization is ketosteroid isomerase (KSI) ( Figure 1). Subjected to both theoretical and experimental interrogations, KSI has one of the highest known unimolecular rate constants 13,14 with many theoretical [15][16][17][18][19][20][21] and experimental [22][23][24][25][26] studies investigating its electrostatic preorganization. KSI catalyzes the isomerization of a steroid by altering the position of a C=C double bond through formation of a charged enolate after a proton abstraction and reinserting the proton two carbons away (Scheme 1).…”
mentioning
confidence: 99%
“…Optimized structures and reaction barriers for the active site of WT-KSI with and without a uniform external electric field were taken from our previous study. 16 Uniform electric fields of magnitude 10 MV/cm were applied one at a time to the system in the directions shown in Additionally, it has been shown that mutating tyrosines involved in the extended hydrogen bonding network surrounding the carbonyl oxygen (Y16, Y32, Y57) to 3−chlorotyrosines can reduce the ! "# to 1/5 of that of the wildtype rate.…”
mentioning
confidence: 99%